Legal Accountability of Police Members Affected by Criminal Cases - Hadi Purnomo (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2021)
Criminal cases involving members of the National Police often raise concerns regarding the professionalism, integrity and image of the police institution. Therefore, this research will explore the legal aspects that underlie the responsibility of Polri members in the context of criminal cases. The responsibility of members of the National Police who commit criminal acts includes responsibility for the code of ethics and criminal responsibility. This research methodology involves normative law regarding the laws and regulations that regulate the legal responsibilities of Polri members. The research results show that legal accountability for Polri members involved in criminal cases has significant implications for the integrity of law enforcement agencies. Criminal cases involving members of the National Police can harm the image of the institution in the eyes of the public, and therefore, law enforcement must be carried out firmly, transparently and in accordance with applicable legal norms. Research also reveals that the concept of the rule of law and the balance between criminal law, Disciplinary Regulations, and the Police Professional Code of Ethics play an important role in maintaining the honor of the institution and providing justice to the community. The research conclusions highlight the need for professionalism of the apparatus, adequate facilities and infrastructure, positive public perception of the law, and the formation of a strong legal culture to create an effective and fair legal environment in maintaining security and public order.